Understanding Antibody Testing for COVID-19 - Jacofsky, David; Jacofsky, Emilia M.; Jacofsky, Marc (The Journal of arthroplasty, 2020)
The orthopedic community has seen the COVID-19 pandemic decimate elective surgical volumes in most geographies. Patients and essential workers, such as health care providers, remain rightfully concerned about how to appropriately begin to return to work and community activity in a safe and responsible manner. Many believe that testing for the presence of antibodies on a widespread scale could help drive evidence-based decision-making, both on an individual and societal scale. Much information, and an equal amount of misinformation, has been produced on antibody testing. Education about the role and science of such testing is critically important for programs to be effectively understood and managed.